2022
DOI: 10.24018/ejbio.2022.3.1.325
|View full text |Cite
|
Sign up to set email alerts
|

Radical Scavenging Activities, Total Reducing Power, Total Phenolic and Flavonoids Contents of Four Common Vegetables

Abstract: Aim: This study aimed at evaluating the antioxidant activities of extracts from four vegetables namely: Beta vulgaris, Raphanus sativus, and two varieties (red and green) of Brassica oleracea. Method: The antioxidant properties of these extracts were assessed using five different methods including 2,2-diphényl 1-picrylhydrazyl (DPPH), Nitrogen Oxyde (NO), total reducing power, total phenolic and flavonoids content. Results: All the four vegetable extracts showed free radical-scavenging activity ag… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 26 publications
0
4
0
Order By: Relevance
“…Contents. Te total Phenolic content was determined using the method described by Singleton and Rossi [19] while the favonoid content was determined using the method described by Djeussi et al [20].…”
Section: Total Phenolic and Flavonoidmentioning
confidence: 99%
“…Contents. Te total Phenolic content was determined using the method described by Singleton and Rossi [19] while the favonoid content was determined using the method described by Djeussi et al [20].…”
Section: Total Phenolic and Flavonoidmentioning
confidence: 99%
“…Generally, increasing extraction time raised the TPC of red cabbage. In the study conducted by Hunaefi (2013) on red cabbage, its total phenolic content was stated as (175.89 ± 15.99 mg GAE.100g fw −1 ).Moreover the total phenolic content of four common vegetables was determined by Djeussi et al (2022) and red cabbage was reported as 4.37±0.32 mg of gallic acid/ gram of dried extract. It was observed that all of the total phenolic content measured at different pH and different times were higher than the value reported by Hunaefi et al and by Djeussi et al Red cabbage extracts showed DPPH scavenging activity with an IC 50 value of 0.21± 0.06 -0.34± 0.01 mg/mL at 1h and with an IC 50 value of 0.34±0.01 -0.94±0.03 mg/mL at 24h.…”
Section: Resultsmentioning
confidence: 99%
“…The Total Phenolic content was determined using the method described by Singleton and Rossi [ 26 ]. While the Flavonoid content was determined using method described by Djeussi et al [ 27 ].…”
Section: Methodsmentioning
confidence: 99%
“…Phenolic content was determined using the method described by Singleton and Rossi [26]. While the Flavonoid content was determined using method described by Djeussi et al [27]. Figure 5 shows the efect of the aqueous and ethanol extract of Khaya grandifoliola on human erythrocytes.…”
Section: Total Phenolic and Flavonoid Contents Te Totalmentioning
confidence: 99%